Analysis of Students' Physical Activity Behavior in Learning and Lecture Activities - Susanto (Indonesian Journal of Sport Management and Physical Education, 2023)
Physical activity is one of the routine activities of a person in a day, various physical activities are carried out with various intensities ranging from light, moderate and heavy activities. Physical activity has an important role in maintaining one's health. The benefits of physical activity from a physiological perspective include: strengthening cardiopulmonary endurance, strengthening muscles, maintaining bone density and as a refreshing activity. The study used a questionnaire that adopted the Global Physical Activity Questionnaire (GPAQ), data analysis using descriptive statistics assisted by SPSS 22. Results: research conducted on students with a total of 52 respondents obtained the following results: 100% stated that doing physical activity that needs to be done, the average duration of doing submaximal physical activity is done 3 times a week, the average duration of doing submaximal physical activity is 62 minutes a week, the average duration of doing maximum activity is done 2 times a week, the average duration of doing maximum activity is done 55 minutes a week. The results of the survey conducted on students averaged 62 minutes a week, below the average sub-maximal activity in a week, so it has not reached the minimum recommended standard according to WHO. Meanwhile, only 9.6% reached the minimum standard according to WHO for 150 minutes